Engaging economics: New Testament scenarios and early Christian reception - Longenecker, Bruce W.; Liebengood, Kelly D. (William B. Eerdmans Publishing Company, 2009)
Introduction / Bruce W. Longenecker and Kelly D. Liebengood -- Methodological issues in using economic evidence in interpretation of early Christian texts / Peter Oakes -- New Testament scenarios -- Money matters : economic relations and the transformation of value in early Christianity / Stephen C. Barton -- Jesus, virtuoso religion, and the community of goods / Brian J. Capper -- The spirit and the "other," Satan and the "self" : economic ethics as a consequence of identity transformation in Luke-Acts / Aaron J. Kuecker -- Agrarian discourse and the sayings of Jesus : "measure for measure" in Gospel traditions and agricultural practices / John S. Kloppenborg -- Was God Paul's patron? : the economy of patronage in Pauline theology / David J. Downs -- The economics of humility : the rich and the humble in James / Mariam Kamell -- Aliens and strangers? : the socioeconomic location of the addressees of 1 Peter / David G. Horrell -- Early Christian reception -- The poor of Galatians 2:10 : the interpretative paradigm of the first four centuries / Bruce W. Longenecker -- Tertullian on widows : a North African appropriation of Pauline household economics / David E. Wilhite -- Critiquing Rome's economy : Revelation and its reception in the Apostolic Fathers / Grant Macaskill -- By almsgiving and faith sins are purged? : the theological underpinnings of early Christian care for the poor / Christopher M. Hays -- Zacchaeus's half : ascetical economy in the Syriac Book of steps / Robert A. Kitchen -- Afterword / Bruce W. Longenecker